Genotypical and phenotypical detection of hemolysin enzyme of Escherichia coli causing urinary tract infections - Azhar N. Hussein; Mithal Kareem Abass AL-Hassani (Al-Qadisiyah Journal of Pure Science, 2018)
The present study included isolation and diagnosis of the bacteria Escherichia coli  from patients suffering urinary tract infection symptoms in different ages and both sexes, which was taken from the consulting  patients in Maternal Hospital, and General Teaching Hospital in AL-Diwianyia  city during the period from 1/3/2012 till 1/8/2012 .                                                                             The results of morphological and biochemical tests appeared that  94  isolates belong to bacteria E. coli , among them 40 (42.6%) isolates were hemolysis on blood agar plates containing human blood ( A, B, AB, O ) and were production percentage of hemolysin (55%, 72.5%, 20%, and 40%) respectively .     Some virulence factors, which bacteria have, were studied in both phenotypical and genotypical . Such as hemolysin production . The results showed that all the bacterial samples 40 (100%) were hemolysin production phenotypically as well as had the chromosomal genes hlyA  and hlyB  40 (100%) and also had the plasmid gene hlyA plasmid  36 (90%) by using the polymerase chain reaction for detection about these genes .     The results of electrophoresis on Agarose gel showed that most of the bacterial isolates contain plasmid bands between one to three 36 (90%) . All  isolates contained one plasmid band large in size, it molecular weight was about 1200 bp 36 (90%) isolate, the plasmid bands distributed among one plasmid band 14 (35%) isolates, two plasmid band 19 (47.5%) isolates, and three plsmid band 3 (7.5%) isolates .     The results of bacterial conjugation showed the possibility of transmitting of plasmids among E.coli  giving isolates and E.coli MM294  receiving strain in complete process . The features of the conjugation cells were studied as having virulence factor phenotypically included hemolysin production, and also were detected about hlyA plasmid   the results showed that isolates were contained of that gene .